(3bdGFO GdYbjGf aj ehQKGJ GdabQ hGdfSjGfs - (3CHh ESMGb HQgGf GdOjf EHQGgje Hf eMeO GdfGLi GdOeTbj,J (B900 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi YdefG eG df fcf fYde hHYO aGdfGLi EHQGgje dg eDda dWja eNJUQ ajg Mhi eG LGA eeG jhQK abQkG hfSjGfkG s
(3BNQgG (B:s
(3heY hbhY djS cd eQI JSde jGgPG GdaJi GdLQI hfSCd Gddg JYGdi GdYGajI hGdMeO ddg GdPi gOGfG Edjg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1354s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs